2019
DOI: 10.1111/twec.12885
|View full text |Cite
|
Sign up to set email alerts
|

BRICS: How important is the exchange rate pass‐through?

Abstract: This paper analyses the exchange rate pass‐through (ERPT) into domestic consumer prices in BRICS (Brazil, Russia, India, China and South Africa) countries from mid‐1990s onwards by using three different econometric approaches (i.e., the single equation approach, the VAR approach and the time‐varying parameter approach). It is also studied the role of macroeconomic determinants in ERPT. Our results suggest that (a) ERPT is higher for the emerging markets with mostly floating exchange rates (Brazil, Russia and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 43 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…They found that long‐run ERPT is complete in Nigeria but incomplete in South Africa. Jiménez‐Rodríguez and Morales‐Zumaquero (2020) use various methodologies, including the time‐varying state‐space model, to examine ERPT into domestic consumer prices for Brazil, Russia, India, China and South Africa (BRICS) countries. The results show that ERPT is higher in Brazil, Russia and South Africa than in China and India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that long‐run ERPT is complete in Nigeria but incomplete in South Africa. Jiménez‐Rodríguez and Morales‐Zumaquero (2020) use various methodologies, including the time‐varying state‐space model, to examine ERPT into domestic consumer prices for Brazil, Russia, India, China and South Africa (BRICS) countries. The results show that ERPT is higher in Brazil, Russia and South Africa than in China and India.…”
Section: Literature Reviewmentioning
confidence: 99%